2013
DOI: 10.1177/0969733012468465
|View full text |Cite
|
Sign up to set email alerts
|

Unethical conduct by the nurse

Abstract: The aim of this study was to uncover and critically examine hidden assumptions that underpin the findings of nurses' unethical conduct arising from inquiries conducted by the Nurses Tribunal in New South Wales. This was a qualitative study located within a post-structural theoretical framework. Transcripts of five inquiries conducted between 1998 and 2003 were analysed using critical discourse analysis. The findings revealed two dominant discourses that were drawn upon in the inquiries to construct nurses' con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Moreover, patients often willingly give up their autonomy in favor of nurses because of total trust within their relationship. Raising accountability and responsibility of nurses for patients might lead to unwanted pressure and result in unethical behavior of nurses (Dixon, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients often willingly give up their autonomy in favor of nurses because of total trust within their relationship. Raising accountability and responsibility of nurses for patients might lead to unwanted pressure and result in unethical behavior of nurses (Dixon, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Papastavrou et al (2014a) found that missing care was directly related to patient risk and poorer outcomes. These concerns focus on patients not receiving the care they need, and nurses placing themselves at professional and legal risk every time they have to ration care (Cox, 2010;Dixon, 2013). Although nurses' workload as a subject in itself, has been examined, particularly in relation to key areas such as quality, job satisfaction, staff turnover and stress (Bail and Grealish, 2016;Bolton, 2000;Bridges et al, 2013;Cimiotti et al, 2012;Glasberg et al, 2007), little has raised concerns around nurses' accountability in care rationing.…”
Section: Introductionmentioning
confidence: 99%